Evaluation of protective efficacy induced by virus-like particles containing a Trichinella spiralis excretory-secretory (ES) protein in mice. Issue 1 (December 2016) - Lee, Su-Hwa; Kim, Sang-Soo; Lee, Dong-Hun; Kim, Ah-Ra; Quan, Fu-Shi
Abstract Background The frequent outbreaks of human trichinellosis globally underscore the need to develop effective vaccine. We hypothesized that a novel vaccine could improve vaccine efficacy againstTrichinella spiralis . Methods In this study, we developed virus-like particles (VLPs) containing the 53 KDa excretory/secretory (ES) protein ofT. spiralis and the influenza matrix protein 1 (M1) as a core protein, and investigated the protective efficacy of the VLPs alone or with cholera toxin (CT) in a mouse model. Results Intramuscular immunization inducedT. spiralis -specific IgG, IgG1 and IgG2a antibody responses before and after challenge infections in the sera. These antibody responses were significantly enhanced in mice immunized with adjuvanted VLPs. Upon challenge infection, vaccinated mice showed significantly reduced worm burden in the diaphragm. Protective immune responses and efficacy of protection were significantly improved by immunization with VLPs together with CT adjuvant. Conclusions Our results are informative for a better understanding of the protective immunity induced byT. spiralis VLPs, and will provide insight into designing safe and effective vaccines.